THE INFLUENCE OF INTEREST IN LEARNING AND STUDENT DISCIPLINE ON LEARNING OUTCOMES MEDIATED BY LEARNING MOTIVATION (STUDY IN SMPN 197 WEST JAKARTA) - Mulyamti, Hastin Suprihatin Mulyamti; Tarumingkeng, Rudy C. (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
This study aims to analyse the effect of student interest and discipline mediated by learning motivation to improve student learning outcomes at SMPN 197 West Jakarta. This study is motivated by the important role of motivation in the learning process and how motivation significantly affects student learning outcomes. Learning interest is considered an important factor that encourages students to actively engage in the learning process, while discipline plays an important role in creating a structured and conducive environment for optimal learning. This study examines the extent to which these two factors - learning interest and discipline - can influence students' motivation and subsequently impact on their learning outcomes. Through a quantitative approach, data was collected from students at SMPN 197 West Jakarta using questionnaires and analysed by statistical methods. The results showed a positive correlation between discipline and their learning motivation. the higher the students' discipline level, the higher their learning motivation level. This effect proved to be statistically significant based on the analysed data. The findings confirm that disciplinary behaviour can be an important driver for individuals to maintain and enhance their drive in the learning process. This study provides valuable insights for educators and policy makers to develop strategies that can enhance students' learning experience, focusing on motivation as an important element in educational success.